Application of Vacuum Frying Machines in Various IKM Banana Processes to Improve Employee Expenses PHK PT Kertas Leces Probolinggo District Provinsi Jawa Timur - Trias Setyowati; Kosjok Kosjok; Wiwik Suharso (OJS Universitas Muhammadiyah Gresik, 2019)
During the rainy season traditional production activities for sale and banana chips cannot be done because the processed raw material for bananas must be dried in the sun for three consecutive days so that the quality is good. This condition is experienced by mother’s wife of former employees of layoffs PT Kertas Leces Faizzah Probolinggo in SMEs, especially at the height of the rainy season in December and January. The weather forecast for BMKG in Probolinggo Regency in January 2017 shows high rainfall of more than 400 mm lasted until March. Therefore, this activity aims to apply a vacuum frying frying machine so that partners can still produce with good quality when it is rainy or cloudy. Vacuum frying can fry the raw material of wet bananas into high quality products and banana chips. The advantages of the vacuum frying method are non-charred products, the nutrient content does not disappear, the taste and aroma according to the original ingredients, crisp, do not need preservatives and artificial flavor enhancers. Whereas the Surya Makmur Farmer Group faces the problem of the price of slash and the location of banana plants below the market price. So that the specific target to be achieved is the strengthening of business units providing processed sale and banana chips with sustainable production and managed by financial management and retail-based marketing by IKM Faizzat, as well as the availability of banana supply at market prices from farmers in the Farmers' Group. The solution provided by the Implementing Team is in the form of machine procurement and testing, production training and mentoring, and socialization. The procurement and testing of vacuum frying machines as frying machines, and spinner machines as oil residues are left over in sale products and banana chips. The training activity begins with the production of standard operating procedures, production training and machine maintenance documents. Socialization activities are given to partners so that they can be continued in the production of various banana processed products independent.